PENERAPAN METODE PETA KONSEP UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPA SISWA KELAS VII B SMP NEGERI 12 YOGYAKARTA - Ernawati Ernawati; Hidayati Hidayati; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
This research was aimed to improve motivation and evaluation of science for grade VII B students through concept map at SMP negeri 12 Yogyakarta in the second semester academic year 2013/2014. This research is Classroom Action Research that was collaboratively. The subject of this study is 34 students in class VII B at SMP Negeri 12 Yogyakarta. Thr object of this study is teaching by using concept map, motivation, and students evaluation. The collecting data method used observation, documentation, questionaire and test. The result of this research showed that after nimplementing concept map, motivation and evaluation grade VIIB students became better and improved. This showed that by improvment of average percentage of learning motivation for each cycle, indicator average of motivation pra cycle is 63,3% improve become 73, 3% in cycle I and 78,7% in cycle II. The average of evaluation in cycle I is 73 become 79 in cycle II. A lot of students can reach the KKM in cycle I are 17 students with 50% persentage. In cycle II become 79,41% one 27 students can reach KKM. Based on the result of the research , the writer gave advice for scince teacher to implement concept map as the variation of teaching and learning method.Â